Analisis Jenis-Jenis Media Pembelajaran di Sekolah Dasar Negeri 09 Sungai Ambawang - Kholili, Kholili; Fatmawati, Risdiana Andika; Farisi, Salman Al (Lembaga Intelektual Muda Maluku, 2025)
This research focuses on the use of audio, visual, and audiovisual media in the learning process from Grade I to Grade VI. The study aims to analyze the types of learning media used by teachers at State Elementary School 09 Sungai Ambawang. This research employs a qualitative approach using observation and interview techniques. The data analysis techniques used are qualitative data analysis, which includes data reduction, data presentation, and drawing conclusions. The research results indicate that audio media are used effectively in Grade I for learning to read poetry and in Grade VI for mixed arithmetic operations, as they support listening skills and enhance students' memory. Visual media are used in Grade II through posters of the human body's organs and in Grade IV through large maps of Indonesia, helping students understand concrete concepts more clearly. Audiovisual media are used in Grade III by showing videos of heroes' struggles and in Grade V with photosynthesis animations, which have proven effective in explaining abstract and narrative materials. The conclusion of this study emphasizes that the selection of learning media is greatly influenced by the stage of students' cognitive development, the characteristics of the material, and the availability of supportive facilities. Teachers are required to be creative, adaptive, and innovative in utilizing media to make the learning process more effective and enjoyable. The findings of this study are expected to serve as a practical reference for elementary school teachers in designing learning strategies that are more meaningful and aligned with students' needs.